Hakekat Peserta Didik dan Pengembangannya - Tasya Fajriani; Caren Patrysha; Fadhillah Khairunnisa (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This journal discusses the nature of students and their development in Islamic education. The nature of students includes an understanding of the nature, characteristics and potential of the individual who is learning. Islamic education aims to develop students holistically, including intellectual, moral, emotional, social and spiritual aspects. Teachers have an important role in understanding students and designing effective teaching strategies. This paper explores the basic concepts of students in Islam, the factors that influence their development, and the role of teachers in optimizing students' potential. The presentation of this paper can provide insight to educators and practitioners of Islamic education to improve the quality of the educational process.